To the question of the CLIL using in teaching foreign languages (Eurasian Journal of Philology Science and Education, 2019)
The article is devoted to some aspects of content and language integrated learning and the possibility of its usage at the university. The purpose of the article is to investigate the methodological aspect ofthe content and language integrated learning. The novelty of the research is related to the fact that theauthors of the paper have conducted a comparative analysis of studied method with other methods ofbilingual education. The paper examines students’ and teachers’ perceptions as they engage with teaching and learning special disciplines in English. Overall, the study recommends the content and languageintegrated learning as a rich cognitive medium for learning, and an asset for promoting quality learningwith the specification that its implementation needs careful context-bound consideration. The studiedmethod is far-reaching in that the present need for cutting-edge methodology in the Kazakhstan calls forrenewed ways of articulating the curriculum to teach subjects and foreign languages